Supporting and Inhibiting Factors in Managing a Sanad-Based Qur’an Memorization Program at STIU Wadi Mubarak Bogor - Lamya Hayatina; Iswan Iswan; Widia Winata (Yapilin Press, 2026)
ABSTRACT This study aims to identify the supporting and inhibiting factors in the sanad-based tahfidz program at STIU Wadi Mubarak Bogor. This research employs a qualitative approach using a case study method, integrating observation, in-depth interviews, and documentation as primary data collection techniques to obtain comprehensive and in-depth findings. The results indicate that the main supporting factors include effective and visionary leadership, competent sanad-certified teachers, strong parental support, the availability of scholarships and donor contributions, students’ intrinsic motivation, and ongoing teacher professional development. These elements interact dynamically and synergistically in shaping a conducive, structured, and sustainable Qur’anic learning ecosystem that supports the quality of memorization. On the other hand, the inhibiting factors consist of psychological-individual dimensions, such as laziness, boredom, decreased motivation, psychological pressure, and health-related issues, as well as structural-systemic dimensions, including tight academic schedules, lack of discipline among participants, and distractions caused by uncontrolled gadget usage. The findings underscore that the success of a sanad-based tahfidz program is highly dependent on comprehensive and balanced management of both psychological and systemic aspects. This study offers practical implications for Islamic educational institutions in formulating strategic policies to improve memorization quality and ensure the sustainability of sanad transmission.